Aktivitas Pemasaran Media Sosial dan Word Of Mouth Terhadap Keputusan Pembelian Konsumen pada Produk Umkm Roti dan Kue di Kabupaten Landak - Sopiana, Mika; Kurniati, Dewi; Suyatno, Adi (Jurnal Social Economic of Agriculture, 2025)
With the development of information technology, akery and cake MSMEs are encouraged to adapt to social media as a marketing medium and increase word of mouth. The purpose of this study is to measure social media marketing activities and word of mouth in influencing purchasing decisions for bakery and cake MSME products. A descriptive approach was used in describing the data and research findings. Structural Equation Modeling analysis was used to measure the relationship between social media and word of mouth variables with 120 respondents who visited bakery and cake MSMEs. The results showed a significant relationship between social media marketing activities and word of mouth on purchasing decisions for bakery and cake MSME products in Landak Regency. Social media plays an important role in disseminating visual content to attract customer attention, while word of mouth occurs naturally by consumers in direct interaction with their family, friends and family regarding their experiences after buying. The findings provide important implications for MSME marketing strategies, indicating the need for greater focus on optimising marketing through social media and not neglecting word of mouth to increase consumer appeal and trust.